Analisis Aspek Desain Ergonomis Tempat Wudu Pada Masjid Islamic Center Lhokseumawe - Muliana, Erna; Olivia, Sisca; Fithri, Cut Azmah; Nurfebruary, Nanda Sitti; Andria, Melly; Nurdin, Erwinsyah (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2025)
The ablution place has an important role in the life of Muslims. Wudu space not only serves as a place to prepare for worship, but also as a manifestation of one of the Islamic values, namely sustainability. Therefore, it becomes important to understand how the ergonomic use of space in the design of the ablution place of the Islamic Center Mosque of Lhokseumawe City as the locus of this observation. The main objective of this study is to analyze the physical-internal factors that influence the design of wudu stations based on the perspective of space ergonomics theory so that wudu stations can be used sustainably. This research uses descriptive-analytical method with qualitative data processing. The results found in the case study are that there are several typologies of wudu spaces that affect user comfort in terms of ergonomics. In addition, the redundancy of water and circulation corridor spaces is a challenge for the sustainability of wudu places. This paper is expected to make a positive contribution to the guidelines for sustainable wudu spaces, as well as provide direction for architects, designers, and developers in creating ergonomic wudu spaces that combine Islamic architecture values with strong sustainability principles.